Best Backpacking Trips in Montana, Wyoming, and Colorado - White, Michael C., 1952-; Lorain, Douglas, 1962- (Book collections on Project MUSE., 2018)
"All the necessary information to plan and execute the best backpacking trips in the US West. The authors have walked every mile of the trails described and take readers into some of the wildest and most scenic backcountry landscapes in the nation and help them plan"--Provided by publisher.